Lower free triiodothyronine (fT3) levels in cirrhosis are linked to systemic inflammation, higher risk of acute-on-chronic liver failure, and mortality - Lukas Hartl; Benedikt Simbrunner; Mathias Jachs; Peter Wolf; David Josef Maria Bauer; Bernhard Scheiner; Lorenz Balcar; Georg Semmler; Michael Schwarz; Rodrig Marculescu; Varius Dannenberg; Michael Trauner; et al. (JHEP Reports, 2024)
Background & Aims: Advanced chronic liver disease (ACLD) may affect thyroid hormone homeostasis. We aimed to analyze the pituitary–thyroid axis in ACLD and the prognostic value of free triiodothyronine (fT3). Methods: Patients with ACLD (liver stiffness measurement [LSM] ≥10 kPa) undergoing hepatic venous pressure gradient (HVPG) measurement between June 2009 and September 2022 and available fT3 levels were included. Clinical stages of ACLD were defined as follows: probable ACLD (pACLD; LSM ≥10 kPa and HVPG ≤5 mmHg), S0 (mild portal hypertension [PH]; HVPG 6–9 mmHg), S1 (clinically significant PH), S2 (clinically significant PH with varices), S3 (past variceal bleeding), S4 (past/current non-bleeding hepatic decompensation), and S5 (further decompensation). Results: Among 297 patients with ACLD, 129 were compensated (pACLD, n = 10; S0, n = 33; S1, n = 42; S2, n = 44), whereas 168 were decompensated (S3, n = 12; S4, n = 97; S5, n = 59). Median levels of thyroid-stimulating hormone (TSH) numerically increased with progressive ACLD stage (from 1.2 μIU/ml [pACLD] to 1.5 μIU/ml [S5]; p = 0.152), whereas fT3 decreased (from 3.2 pg/ml [pACLD] to 2.5 pg/ml [S5]; p <0.001). Free thyroxin levels remained unchanged (p = 0.338). TSH (aB 0.45; p = 0.046) and fT3 (aB -0.17; p = 0.048) were independently associated with systemic C-reactive protein levels. Lower fT3 was linked to higher risk of (further) decompensation (adjusted subdistribution hazard ratio [asHR] 0.60; 95% CI 0.37–0.97; p = 0.037), acute-on-chronic liver failure (asHR 0.19; 95% CI 0.08–0.49; p <0.001) and liver-related death (asHR 0.14; 95% CI 0.04–0.51; p = 0.003). Conclusions: Increasing TSH and declining fT3 levels are observed with progressive ACLD stages. The association of TSH and fT3 with systemic inflammation suggests a liver disease-associated non-thyroidal illness syndrome. Lower fT3 levels in patients with ACLD indicate increased risk for decompensation, acute-on-chronic liver failure, and liver-related death. Impact and Implications: In a large well-characterized cohort of patients with advanced chronic liver disease (ACLD), we found a decline of free triiodothyronine (fT3) throughout the clinical stages of ACLD, paralleled by a numerical increase of thyroid-stimulating hormone (TSH). This suggests a progressive development of a non-thyroidal illness syndrome in association with ACLD severity. Importantly, C-reactive protein independently correlated with TSH and fT3, linking thyroid dysbalance in ACLD to systemic inflammation. Lower fT3 indicated an increased risk for subsequent development of hepatic decompensation, acute-on-chronic liver failure, and liver-related death. Clinical trial number: Vienna Cirrhosis Study (VICIS; NCT: NCT03267615).